Diagnosis of Spinal Column Abnormalities by Image processing of Reflective Markers Set on Spinus Process - mohammad yousefi; saeed Il Begi; naser Mehrshad; mohammadesmail afzalpoor (Sport Sciences and Health Research)
The aim of the present study was to introduce a non-invasive method (image processing) to measure lumbar lordosis and thoracic kyphosis. The advantages of this method are fast measurement and no direct contact with the subjects. For this purpose, 40 male students (age: 26±2 years old, weight: 72±2.5 kg, and height: 169±5.5 cm) volunteered to identify these advantages and the accuracy of the suggested method. The lumbar lordosis and thoracic kyphosis of all subjects were extracted and compared using the suggested method as well as the flexible ruler method (control). Findings of this research were analyzed by descriptive statistics and Pearson correlation coefficient. The results showed that the correlation of the suggested and flexible ruler methods to measure lumbar lordosis and thoracic kyphosis were 0.95 and 0.97 respectively. These results indicated that the suggested method could be used effectively to measure lumbar lordosis and thoracie kyphosis and was valid compared with the flexible ruler. So image processing method can be used as a non-invasive method along with the other methods.